Reklama a style funkcjonalne języka. Zarys problematyki - Cieciura, Piotr (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2009)
Autor prezentuje zarys szerokiego zagadnienia reklamy wobec stylów funkcjonalnych języka. Na początku przytacza cele komunikatu reklamowego opracowane przez znanych lingwistów J. Brabca i J. Bralczyka. Następnie autor prezentuje przegląd stanowisk językoznawców czeskich i polskich na temat przynależności tekstów reklamowych do danego stylu języka (styl publicystyczny, administracyjny, artystyczny bądź samodzielny styl reklamy), by ostatecznie dojść do wniosku, że pytanie o styl tekstów reklamowych pozostaje otwarte.

The author presents an outline of a wide issue of advertisement towards the styles of language functioning. At the beginning she presents the aims of advertising communication worked out by the well-known linguists, namely: J. Brabec i J. Bralczyk. Next, the author presents a review of the Czech and Polish positions of linguists concerning the adjunction of the advertising texts to a given language style (feature style, administrative, artistic or individual style of advertisement) in order to reach a conclusion, that there is still an open question concerning the style of the advertising texts.
Advertising and functional styles of language. An outline of issues
Keywords: język czeski; Czech language; style funkcjonalne; functional styles of language; reklama; advertising; styl publicystyczny; journalistic style